MII (M = Mn, Fe, Co, Ni and Cu) complexes with a chromone-derived neutral ligand: synthesis, structural characterization, photocatalytic and mycobacterial activity studies. (19th January 2022) - Camargo, Mariana Leticia Munin; Schwalm, Cristiane Storck; Bortolotto, Tanize; de Freitas Daudt, Natália; Rossi, Grazielle Guidolin; Anraku de Campos, Marli Matiko; D'Oliveira, Kaique Alexandre; Cuin, Alexandre; Schwade, Vânia Denise
Abstract : This work provides the coordination chemistry of the resulting compound of 2-(2-furyl)-3-hydroxychromone and nicotinoyl chloride with first row transition metal ions. Good performance in H2  evolution was shown by the copper-containing photocatalyst. Abstract : The reaction of 2-(2-furyl)-3-hydroxychromone and nicotinoyl chloride produces a neutral ligand (L ), which has nitrogen and oxygen donor atoms. Evidence of L polymorphism is discussed. The new molecule showed fluorescence emission in solution and in the solid state (intense emission at 556 nm [ λ exc 392 nm] in the solid state). Ligand L and coordination compounds [MCl2 (L)2 ] n (M = Mn (1 ), Fe (2 ), Co (3 ), Ni (4 ) and Cu (5 )) and [Cu(NCS)2 (L)2 ] n (6 ) were characterized using spectroscopic techniques. The crystal structures were determined via single-crystal X-ray diffraction and powder X-ray diffraction. Biological tests with mycobacterial strains were conducted for compounds 1–5 . The optical band gap energies of these compounds, which ranged from 3.29 to 3.39 eV, were estimated from diffuse reflectance spectroscopy data. Mesoporous TiO2 -based photocatalysts were prepared and tested for hydrogen production. The m-TiO2 -5 photocatalyst produced hydrogen at a 1052.5 μmol g −1 h −1 rate under irradiation using a 300 W Hg/Xe lamp.